Diverse profiles of N‐acyl‐homoserine lactone molecules found in cnidarians. Issue 2 (21st November 2013) - Ransome, Emma; Munn, Colin B.; Halliday, Nigel; Cámara, Miguel; Tait, Karen
Abstract Many marine habitats, such as the surface and tissues of marine invertebrates, including corals, harbour diverse populations of microorganisms, which are thought to play a role in the health of their hosts and influence mutualistic and competitive interactions. Investigating the presence and stability of quorum sensing (QS) in these ecosystems may shed light on the roles and control of these bacterial communities. Samples of 13 cnidarian species were screened for the presence and diversity of N‐acyl‐homoserine lactones (AHLs; a prevalent type of QS molecule) using thin‐layer chromatography and an Agrobacterium tumefaciens NTL4 biosensor. Ten of 13 were found to harbour species‐specific, conserved AHL profiles. AHLs were confirmed in Anemonia viridis using liquid chromatography tandem mass spectrometry. To assess temporal role and stability, AHLs were investigated in A. viridis from intertidal pools over 16 h. Patterns of AHLs showed conserved profiles except for two mid‐chain length AHLs, which increased significantly over the day, peaking at 20:00, but had no correlation with pool chemistry. Denaturing gel electrophoresis of RT‐PCR‐amplified bacterial 16S rRNA showed the presence of an active bacterial community that changed in composition alongside AHL profiles and contained a number of bands that affiliate with known AHL‐producing bacteria. Investigations into the quorum sensing‐controlled, species‐specific roles of these bacterial communities and how these regulatory circuits are influenced by the coral host and members of the bacterial community are imperative to expand our knowledge of these interactions with respect to the maintenance of coral health.